Kreativitas Anak Usia Dini pada Strategi Pembelajaran Berbasis Proyek Menggunakan Bahan Bekas di KB Mutiara Bunda Bumiayu - Mujayana, Mujayanah; Muhtarom, Muhtarom; Handayani, Arri (Universitas PGRI Semarang, 2025)
The background of this research is that some children have inhibited creativity development because they have difficulty in conveying ideas and concepts during the learning process. Some children are less interested in creative activities. The objectives of this study are: 1) to determine the creativity of early childhood through project-based learning strategies using used materials at KB Mutiara Bunda Bumiayu; 2) to determine the supporting and inhibiting factors of early childhood creativity through project-based learning strategies using used materials at KB Mutiara Bunda Bumiayu. This study uses qualitative research with a survey design. Primary data sources were obtained from early childhood group B. Data collection used observation, interviews, and documentation. Data validity testing used data credibility with technical triangulation. Data analysis techniques used qualitative descriptive. The results of the study showed that: 1) early childhood group B at KB Mutiara Bunda Bumiayu has creativity in making underwater decorations using used materials through a project-based learning model. Children have imagination in making underwater decorations using used materials, such as: used cardboard, used styrofoam, glue, white paper, small stones, pictures of fish, and plastic grass. Children dare to try making underwater decorations using used materials. Children can explore underwater conditions through TV shows and YouTube. Children can turn used materials into underwater decorations. 2) Supporting factors for the development of children's creativity, namely children get motivation, direction, materials, and tools to make underwater decorations from teachers. 3) Inhibiting factors for the development of children's creativity, namely children need a lot of time to express ideas in decorating the underwater using used materials. The suggestion of this study is that children should be able to utilize used materials, so that they get works that can increase their creativity. Children should be more active in learning through project-based learning strategies using used materials.